Phosphatidylinositol Kinases and Phosphatases in Entamoeba histolytica - Nakada-Tsukui, Kumiko; Watanabe, Natsuki; Maehama, Tomohiko; Nozaki, Tomoyoshi (Frontiers in Cellular and Infection Microbiology, 2019)
Phosphatidylinositol (PtdIns) metabolism is indispensable in eukaryotes. Phosphoinositides (PIs) are phosphorylated derivatives of PtdIns and consist of seven species generated by reversible phosphorylation of the inositol moieties at the positions 3, 4, and 5. Each of the seven PIs has a unique subcellular and membrane domain distribution. In the enteric protozoan parasite Entamoeba histolytica, it has been previously shown that the PIs phosphatidylinositol 3-phosphate (PtdIns3P), PtdIns(4,5)P2, and PtdIns(3,4,5)P3 are localized to phagosomes/phagocytic cups, plasma membrane, and phagocytic cups, respectively. The localization of these PIs in E. histolytica is similar to that in mammalian cells, suggesting that PIs have orthologous functions in E. histolytica. In contrast, the conservation of the enzymes that metabolize PIs in this organism has not been well documented. In this review, we summarized the full repertoire of the PI kinases and PI phosphatases found in E. histolytica via a genome-wide survey of the current genomic information. E. histolytica appears to have 10 PI kinases and 23 PI phosphatases. It has a panel of evolutionarily conserved enzymes that generate all the seven PI species. However, class II PI 3-kinases, type II PI 4-kinases, type III PI 5-phosphatases, and PI 4P-specific phosphatases are not present. Additionally, regulatory subunits of class I PI 3-kinases and PI 4-kinases have not been identified. Instead, homologs of class I PI 3-kinases and PTEN, a PI 3-phosphatase, exist as multiple isoforms, which likely reflects that elaborate signaling cascades mediated by PtdIns(3,4,5)P3 are present in this organism. There are several enzymes that have the nuclear localization signal: one phosphatidylinositol phosphate (PIP) kinase, two PI 3-phosphatases, and one PI 5-phosphatase; this suggests that PI metabolism also has conserved roles related to nuclear functions in E. histolytica, as it does in model organisms.